The importance of having an inventory control system for the presentation of financial information for small businesses. - Leidy Johana Posada Moreno; Orlando Carmelo castellanos polo (MultiTech Publisher, 2020)
The purpose of this investigation is to publicize the importance for small companies to implement an inventory control system for the presentation of their financial statements. In many cases, one may come to think that accounting should be applied to large companies and that small-scale businesses do not need it, but the reality is different, based on the fact that accounting seeks to provide the same objective for all companies, to control the resources and generate profits that help them to remain in time, in favor of this and to achieve a contextual knowledge of the study, a brief historical review of accounting is carried out from its origin, reaching the implementation of IFRS